Kajian Biomekanika Untuk Jalan Cepat Terhadap Rancangan Knee Joint Sistem Energy Storing Mekanisme 2 Bar Pada Kaki Prosthetic Endoskeletal Bagi Amputee Transfemoral - Herdiman, Lobes; Damayanti, Retno Wulan; Faiz, Zulfa Miftakhul (Program Studi Teknik Industri, Universitas Sebelas Maret, 2012)
Endoskeletal prosthetic foot that was developed at the knee joint by storing energy systems 2 bar mechanism. This technology is analogous to a spring that can be stretched and loosened, store and release elastic potential energy. Storing energy systems to facilitate the activity of normal or brisk walking. 2 bar mechanism consists of two links and a joint with joint function as a link 2 link. Storing energy in the system design of knee joint using a gas spring with the principle of increasing the pressure causes compression of nitrogen gas in the tube and the more energy saved. This study involves a transfemoral amputee object, male gender, age 49 years, height 164 cm, and weight 67.5 kg (without a prosthetic foot). Kadaba's experimental protocol using a protocol with a prosthetic foot on the right and left foot on the normal road speed 0.7 m/s - 1.4 m/s. Study the biomechanics of gait cycle analysis for a brisk walk, torque (Ï„), style (Fx, Fy) and external work (Ew). Knee joint with energy storing mechanism of 2 bar to perform flexion and extension movements, swinging his legs no longer require a large force. This system has been storing energy and energy release in shaping the pattern of walking to be balanced at the moment pre swing and mid swing.